ICFF: a cloud forensics framework under the IaaS model - Ya-long XIE; Li-ping DING; Yu-qi LIN; Xiao-ke ZHAO (Tongxin xuebao)
Technical challenges of cloud forensics was summarized and a forensics framework under an infrastructure as a service(IaaS) cloud model called ICFF was proposed.Then,this framework on the open source IaaS cloud platform Eucalyptus was implemented.Finally,a test case to demonstrate the effectiveness of ICFF was designed.Experiments show that the framework can obtain evidence data in cloud platform effectively and efficiently.